Familial pulmonary hypertension. Evidence of autosomal dominant inheritance. Issue 6 (November 1970) - Thompson, P; McRae, C
Abstract : A patient with primary pulmonary hypertension is the fourth member of a family proven to have the disease. The patient's father married twice; the disease appeared in both families, and was transmitted through two generations. Multiple genetic and environmental factors may result in pulmonary hypertension, but the distribution of cases in this family and in others reported is consistent with the autosomal dominant inheritance of a single genetic trait.